The Double-Victimization of Criminalized Women in Neoliberal Contexts: The Case of Paraguay - Galeano Monti, José (Women & criminal justice, 2021)
Rates of female incarceration have markedly increased since the global ascendance of neoliberalism. Drawing on quantitative prison census data and qualitative analysis of inmate interviews, this article asks: Are women rendered vulnerable by neoliberal policies more likely to be victimized by state agents when under their control? We interrogate this using the case of Paraguay – positing that paradigmatically neoliberal regimes systematically incarcerate the precarious, and enact physical and emotional violence against them during incarceration. Findings confirm this reality, with marginalized women disproportionately incarcerated, and disproportionately likely to be abused while in custody. This article advances knowledge about criminalization in neoliberal contexts.